Zmiana klasyfikacji gruntów jako sposób na zwiększenie dochodów budżetowych (na przykładzie gminy Wodzierady) - Bury, Piotr (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Each local government should run its own financial policy. This can be done, apart from a number of individually diversified factors, within limitations imposed by the national law. In Poland even in the case of so-called own revenue sources, it leaves not much discretion to local governments. And recent modifications of the most important local taxes have caused a significant drop in the tax-yield. A way to increase the budget income is then an increasing the local tax-base. One of possible means appeared a change in land classification: from agricultural to "other" what means a shift from a relatively low tax on agriculture to a much higher property tax. An example from a small rural municipality of Wodzierady proves, however, that such a trick is not enough as to compensate the former loss and that much deeper changes in taxation of the land properties are necessary. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 462-468